Study on effects of surface modification on poly(Methyl Methacrylate) (PMMA) surface / Wan Nurlina Wan Yahya - Wan Nurlina, Wan Yahya (2012)
This report presents study on photochemical and wet chemical surface modifications of poly(methy methacrylate) (PMMA) by means of UV (ultraviolet) irradiation and NaOH (sodium hydroxide), respectively. The PMMA solid substrate was prepared by PMMA solution casting on glass wafer resulting in PMMA thin films and commercial PMMA sheets. Both kinds of solid substrate were subjected to two different surface modifications techniques so as to yield carboxylic acid groups that enhanced PMMA surface hydrophilicity. The changes of surface properties of PMMA upon modifications were studied by non-spectral analyses which were contact angle measurement and Toiludine Blue (TB) assay. The findings reveal that both modifications techniques had increased the contact angle value by showing more hydrophobic water drop. On top of that, no carboxyl functional group was produced as confirmed by chemical surface analysis, TB. Considering the various factors, the increasing hydrophobicity is primarily due to surface roughness either pre- or post-treatment. Hence, spectral analysis is strongly recommended to verify each step of modifications in a more precise and accurate manner.